Copper Serum Levels in the Hemodialysis Patient Population - Guido Gembillo; Luigi Peritore; Vincenzo Labbozzetta; Alfio Edoardo Giuffrida; Antonella Lipari; Eugenia Spallino; Vincenzo Calabrese; Luca Visconti; Domenico Santoro (Medicina)
Copper is an essential element in the diet of mammals, including humans. It plays an important role in the physiological regulation of various enzymes and is consequently involved in several biological processes such as angiogenesis, oxidative stress regulation, neuromodulation, and erythropoiesis. Copper is essential for facilitating the transfer of iron from cells to the bloodstream, which is necessary for proper absorption of dietary iron and the distribution of iron throughout the body. In particular, patients with end-stage renal failure who require renal replacement therapy are at increased risk for disorders of copper metabolism. Many studies on hemodialysis, peritoneal dialysis, and kidney transplant patients have focused on serum copper levels. Some reported mild deficiency, while others reported elevated levels or even toxicity. In some cases, it has been reported that alterations in copper metabolism lead to an increased risk of cardiovascular disease, malnutrition, anemia, or mielopathy. The aim of this review is to evaluate the role of copper in patients undergoing hemodialysis and its potential clinical implications.